Comparison of Tuberculin Skin Test result and interferon gamma response to human PPD in BCG scar positive and negative children - Shirin Sayyahfar; Abdollah Karimi; Alireza Fahimzad; Ahmad Reza Shamshiri (Springer, 2019)
Background: The aim of this study is to compare Tuberculin Skin Test (TST) result and interferon gamma response to human PPD (purified protein derivative), in scar positive and scar negative BCG-vaccinated children. Methods: Between August 2007 and May 2008 a total of 236 children aged 1-168 months (mean 21 months) admitted to Mofid Children's Hospital, Tehran, Iran, were enrolled in a cross-sectional study. Each patient was examined for BCG vaccine scar and tested with TST and human PPD-based Interferon Gamma Release Assay (IGRA). Results: Two hundred and twenty one cases out of 236 (44% female, 1-168 months, mean age 21 months) were scar positive of whom 95% TST result was negative. Human PPD-based IGRA was positive in 110 (49.8%), negative in 85 (38.4 %) and indeterminate in 26 (11.8%) of scar positive patients. Fifteen children (40% female, 1-156 months; mean age 42 months) were scar negative. All the scar negative cases were TST negative. Human PPD-based IGRA was positive in 10 (66.7%), negative in 4 (26.7%) and indeterminate in 1 (6.7%) of scar negative patients. Conclusions: Immune responsiveness to human PPD antigens in scar positive and negative children may not correspond with results of the Tuberculin Skin Test.